2012
DOI: 10.3341/kjo.2012.26.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Bevacizumab on Extraocular Muscle in a Rabbit Model

Abstract: PurposeThe purpose of this study was to investigate the myotoxicity of bevacizumab on extraocular muscles in a rabbit model.MethodsThirty New Zealand white rabbits were used for this study. The animals were evenly divided into two groups. In the first group, 15 rabbits were treated with intramuscular injections of bevacizumab (1.25 mg/0.05 mL) in the right superior rectus muscle and normal saline solution (0.05 mL) in the left superior rectus muscle. In the second group, 15 rabbits were treated with subconjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Bevacizumab's effectiveness and safety profile has been confirmed through many preclinical studies, including in vivo studies in numerous species. Many of these have shown that the repeated intravitreal injections of bevacizumab or ranibizumab have no long-term deleterious effects on the electrophysiological and morphologic integrity of the retina [1,[11][12][13][14][15][16][17]. Another preclinical in vivo study reported that after Choroidal Neovascularization (CNV) induction through retinal photocoagulation, PRO-169 administration (1.25 mg per eye) can inhibit the retinal thickness and fluorescein leakage area without toxic effect or adverse events in a rhesus monkey model [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab's effectiveness and safety profile has been confirmed through many preclinical studies, including in vivo studies in numerous species. Many of these have shown that the repeated intravitreal injections of bevacizumab or ranibizumab have no long-term deleterious effects on the electrophysiological and morphologic integrity of the retina [1,[11][12][13][14][15][16][17]. Another preclinical in vivo study reported that after Choroidal Neovascularization (CNV) induction through retinal photocoagulation, PRO-169 administration (1.25 mg per eye) can inhibit the retinal thickness and fluorescein leakage area without toxic effect or adverse events in a rhesus monkey model [4].…”
Section: Introductionmentioning
confidence: 99%